Answers

The Brainliest Answer!
2015-02-21T09:42:31+05:30
In triangle AOD and COE,
OA=OC
OD=OE
AD=CE
hence,they r congr.t
now,
OAD=OCE (CPCT)
ODA=OEC ( " )
also,
OAD=ODA
i.e. OAD=OCEO=DA=OEC
let them be 'x'
now,
in tri.OAC
OA=OC,so,it's an iso.tri.,let their equal ang's be 'a'
llly
let the equal ang's of ODB be 'y'
 ADEC is a cyclic quad.
now,
AOC=180-2a
DOE=180-2y
DOE-AOC=180-2y-(180-2a)
= -2y+a / 2a-2y
2a-2y= 2a-(360-4x-2a)
       =2a-360+4x+2a
       4a+4x-360
ang.B=180-(180-x-a)-(180-x-a)
         =180-180+x+a-180+x+a
=2x+2a-180
i.e,measure of ang.B/difference = 2x+2a-180/4x+4a-360 =1/2
HENCE THE PROOF.. :)
2 5 2